Cancellation Of Notarial Deeds Made By Notaries Done Unauthorized And Against The Law (Case Study In Tangerang City) - Futri, Futri Wicaksono BR Surbakti; Sadjarwo, Isyana Wisnuwardhani; Pulungan, Muhammad Sofyan (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2021)
ABSTRACT A notary as a public official is a profession to provide legal services to the community, a notary who has been appointed by the state is authorized to make evidence or legal documents in the eyes of the law. Legal evidence is made by a Notary in the form of an Authentic Deed or Notary Deed, which has legal and perfect evidentiary power in the eyes of the law. Therefore, the role of the Notary in making the Authentic Deed is very important for the needs of the community, many of which are state documents. Therefore, the precautionary principle is very necessary in carrying out the duties as a Notary. The problem is how a notary produces an authentic deed that is legal and not against the law. What is the responsibility of a notary as a public official for the cancellation of a deed made because it is illegal and against the law? against the law ? To answer these problems, this type of research is normative. The data used are secondary data, library study data collection, and qualitative data analysis and drawing conclusions using deductive methods. The conclusion of this author states that (1) Notaries give birth to Authentic Deeds that are valid and not against the law by having the power of a perfect and binding Proof of Authenticity of Deeds, (2) As a Notary must have an attitude of responsibility for what he has made, if at the time it occurs dispute or violation of the deed he made, the Notary must be responsible for the mistakes he made. and (3) All deed documents made by a Notary/PPAT in Tangerang are null and void or at least legally flawed and against the law. Keywords : Cancellation of Notary Deed, Notary, Notary Liability.